“Modelo de costos por proceso para la producción de baby banano en la finca La Ambateñita del recinto San Pablo de Maldonado, cantón la maná, provincia de Cotopaxi, 2021.” - Masapanta Miranda, Yanina Dayana (2021)
This project was focused on making a cost model per process for the production of baby banana in the “Ambateñita” farm of the San Pablo de Maldonado enclosure in La Maná canton, Cotopaxi province. Methods and instruments that allowed to obtain truthful and reliable information on the productive stages, inputs, human resources, among others, one of the modalities that was used was bibliographic, field, accompanied by the interview with the owner and the observation matrix. Once well understood about the agricultural activity, the development of the cost model according to the needs of the farm was carried out, thus determining the production costs of each process, resulting in a production of 12,480 boxes of gold annually with the value at the sale of 3.50 each, the total and unit costs for each process are; The first does not appear with values due to its initial investment, in the second it is $ 11,215.50 and $ 0.90 per unit, the third is $ 18,463.90 and $ 1.48 per unit. Finally, the total costs are $ 29,679.40, revealing its net profit, which is $ 12,645.42, generating a profit of $ 1.12 per box, and in percentage terms 32.29%. Thanks to the study implemented, the owner of the farm will be able to have a greater organization in his agricultural activity, a better control of his resources, increase profits, reduce costs-expenses, and improve decision-making.